Brain tumours in the time of COVID-19: An online survey on patients’ disease experience in one Italian region - Abete-Fornara, Giorgia; Mameli, Francesca; Ruggiero, Fabiana; Meessen, Jennifer; Blanda, Adriana; Ampollini, Antonella; Locatelli, Marco; Salmaggi, Andrea; Di Cristofori, Andrea; Mauri, Ilaria; Caroli, Manuela (Frontiers in Oncology, 2023)
Background Since the outbreak, in 2019, of COVID-19, the world has experienced marked changes in daily habits, partly reflecting the exceptional social restrictions and health measures adopted to contain the disease. All these measures significantly affected not only peoples’s daily lives and psychological well-being but also the possibility for the healthcare system to function properly. In this setting, brain tumour patients were at risk due to their higher physical and mental fragility and their need for regular care. The aim of the present study was to assess, using a self-reported online questionnaire, the patients’s perceptions regarding their disease experience. Materials and methods We developed an online anonymous self-report survey to assess patients’s disease experience during the pandemic. We investigated the impact of the COVID-19 pandemic on patients’s cancer care schedules, their psychological distress and emotions felt during the pandemic, their levels of worry about COVID-19, and their oncological conditions. Results 107 patients answered our survey, most of them suffering from a glioma. Less than one-third of the sample had their appointments cancelled, delayed or converted into online visits due to the pandemic. Of the patients who answered the survey, 95% declared they were satisfied with their Institute’s oncological management. The feelings reported most often were peacefulness or anxiety/worry; the majority of the sample reported high levels of loneliness, which tended to increase with age, whilst the psychological distress was correlated with age and with having a recurrence of the disease. Half of the sample declared severe worry about their oncological condition, in particular subjects with a recurrence or who were receiving adjuvant therapies. Patients with recurrence tended to worry more about the possibility of contracting COVID-19, and its effects. Conclusion Our findings illustrate how fragile and in need of care patients with a brain tumour may be, especially those with more severe clinical conditions. These data may help boost healthcare professionals’s knowledge about brain tumour patients’s needs and fears, so as to be able to offer them a better hospital experience and improve their clinical management, while possibly also reducing the psychological burden on patients and their families.